1993
DOI: 10.1016/0928-8244(93)90020-5
|View full text |Cite
|
Sign up to set email alerts
|

The ability of peripheral blood mononuclear cells of rabbits infected with Treponema pallidum to produce IL-2

Abstract: It was previously found that the cell-mediated immune response involved in protection against Treponema pallidum is distinctly suppressed during some periods in the course of syphilis infection in rabbits. This may be a result of the weak ability of cells to produce Interleukin-2 (IL-2) as well as of IL-2 absorption. The ability of peripheral blood mononuclear cells (PBMC) of syphilitic rabbits to produce IL-2 develops within the first two weeks after infection reaching a maximum in about the eleventh week. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Because most treponemes cannot be grown in vitro and because T. pallidum, the causative agent of human syphilis, is known to infect rabbits, the laboratory rabbit has been extensively used as a model of human syphilis (22,83,474,530,587). Consequently, a considerable body of information has been gathered on T. pallidum infections of rabbits, and cautious extrapolation to T. cuniculi is possible.…”
Section: Dermal Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Because most treponemes cannot be grown in vitro and because T. pallidum, the causative agent of human syphilis, is known to infect rabbits, the laboratory rabbit has been extensively used as a model of human syphilis (22,83,474,530,587). Consequently, a considerable body of information has been gathered on T. pallidum infections of rabbits, and cautious extrapolation to T. cuniculi is possible.…”
Section: Dermal Systemmentioning
confidence: 99%
“…By using the rabbit-T. pallidum model, it has been demonstrated that the development of immunity is extremely complex and involves a composite of both stimulation and down-regulation (207). Mononuclear cells from rabbits chronically infected with T. pallidum may lose the ability to produce or bind IL-2 (530). Spleen cells of rabbits infected with T. pallidum produce antitreponemal lymphotoxins.…”
Section: Dermal Systemmentioning
confidence: 99%
“…89 Previous studies have shown that there are high amounts of cytokines (IL-2, IL-6, IFNγ, TNF-α, IL-12, IL-17, IL-10, IL-23 and chemokines MCP-1, CXCL10, CX3CR1) existing in the lesions of primary and secondary syphilis or peripheral serum. [68][69][70][71][72][73]90 Under pathological conditions, certain pro-inflammatory mediators, especially TNF-α and IL-1β, may exacerbate ECD by upregulating the expression of adhesion molecules such as VCAM-1, ICAM-1, E-selectin and MCP-1, thereby promoting the adhesion and migration of leukocytes onto the endothelium. 91 In addition, IL-17, IFN-γ and CXCL13 are also abnormally highly expressed in peripheral blood and cerebrospinal fluid (CSF) of patients with neurosyphilis.…”
Section: T Pallidum-mediated Inflammatory Response Via Cytokinesmentioning
confidence: 99%
“…Cytokines include proteins from the tumour necrosis factor (TNF) family, interleukins, and chemokines 89 . Previous studies have shown that there are high amounts of cytokines (IL‐2, IL‐6, IFN‐γ, TNF‐α, IL‐12, IL‐17, IL‐10, IL‐23 and chemokines MCP‐1, CXCL10, CX3CR1) existing in the lesions of primary and secondary syphilis or peripheral serum 68–73,90 . Under pathological conditions, certain pro‐inflammatory mediators, especially TNF‐α and IL‐1β, may exacerbate ECD by upregulating the expression of adhesion molecules such as VCAM‐1, ICAM‐1, E‐selectin and MCP‐1, thereby promoting the adhesion and migration of leukocytes onto the endothelium 91 .…”
Section: T Pallidum‐mediated Ecdmentioning
confidence: 99%